2021
DOI: 10.1111/ggi.14318
|View full text |Cite
|
Sign up to set email alerts
|

Association of vision and hearing impairments with quality of life among older adults: Mediation by psychosocial factors

Abstract: Aim: Vision impairment (VI) and hearing impairment (HI), alone or in combination (dual sensory impairment [DSI]), are common in older adults. We determined (i) the association of vision and hearing, and of VI only, HI only and DSI, with three psychosocial variables (social network, loneliness, depressive symptoms) and with quality of life (QoL), and (ii) whether the considered psychosocial variables mediate the association of VI only, HI only and DSI with QoL among older adults.Methods: Cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Although HI, VI and DSI all have direct effects on QoL, they also have indirect effects that are generated by the compromised physical function. Simning et al (2019) and Phua et al (2022) call for investigators to clarify the mechanisms involved in the impact of SI on QoL. Thus, we focused on the mediating role of physical function in older adults with different types of SI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although HI, VI and DSI all have direct effects on QoL, they also have indirect effects that are generated by the compromised physical function. Simning et al (2019) and Phua et al (2022) call for investigators to clarify the mechanisms involved in the impact of SI on QoL. Thus, we focused on the mediating role of physical function in older adults with different types of SI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Harithasan et al (2020) found an association between SI and lower scores on surveys about QoL. A recent study using data from the Transitions in Health, Employment, Social Engagement and Intergenerational Transfers in Singapore Study (THE SIGNS Study) found that HI, VI and DSI were associated with lower QoL (Phua et al, 2022). A review study found a significant association between SI and QoL, with an increase in HI or VI severity resulting in a lower QoL (Tseng et al, 2018).…”
Section: The Impact Of Sensory Impairment On Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Participants without vision and hearing impairments were defined as the absence of vision and hearing impairments. Conversely, participants with vision and hearing impairments were defined as having both vision and hearing impairments ( 5 , 17 , 18 ). To represent vision and hearing status, three types of independent variables were defined as follows: (1) the three questions included eyesight for seeing things at a distance (1 = excellent, 2 = very good, 3 = good, 4 = fair, and 5 = poor), eyesight for seeing things up close (1 = excellent, 2 = very good, 3 = good, 4 = fair, and 5 = poor), and hearing (1 = excellent, 2 = very good, 3 = good, 4 = fair, and 5 = poor); (2) vision and hearing impairments were divided into four groups (1 = no vision and hearing impairments, 2 = only vision impairments, 3 = only hearing impairments, and 4 = both vision and hearing impairments); and (3) three questions were combined to obtain vision and hearing scores (as a continuous variable) ranging from 3 to 15, with the highest score representing both vision and hearing impairments.…”
Section: Methodsmentioning
confidence: 99%
“…Participants without vision and hearing impairments were defined as the absence of vision and hearing impairments. Conversely, participants with vision and hearing impairments were defined as having both vision and hearing impairments (5,17,18). To represent vision and hearing status, three types of independent variables were defined as follows:…”
Section: Assessment Of Vision and Hearing Statusmentioning
confidence: 99%